Transnational identities as a pathway to genuine universalism: an approach between Léopold Senghor and Darcy Ribeiro (mediated by Gilberto Freyre and Leopoldo Zea) - Pereira da Silva, Fabricio (2023)
This article proposes to compare négritude [blackness] in Léopold Senghor and Latin Americanism in Darcy Ribeiro. We are mainly interested in pointing out how the notion of “civilization” brings the two authors closer: the understanding of black African civilization as a constitutive part of a future “civilization of the universal” in Senghor, and the idea of “emerging civilization” in Ribeiro. The key to the comparison (and approximation) between the two lies in their uses of civilization. And this becomes more evident when Gilberto Freyre and Leopoldo Zea are engaged in this dialogue. We are particularly interested in facilitating this meeting using the “Lusotropical” Freyre, who in his reflection also refers to a global meeting of civilizations, and the Zea of América en la historia, who, himself a reader of Freyre, seeks to define America’s place based on a critical re-reading – via Toynbee – of Hegel’s philosophy of history. The article is intended as a contribution to the history of ideas (or intellectual history), as well as an invitation to dialogue with more philosophical approaches aimed at discussing ways of thinking about the unity and diversity of cultures and, in particular, the place of non-European peoples in history.